2015
DOI: 10.1002/2014ja020890
|View full text |Cite
|
Sign up to set email alerts
|

Influence of local ionization on ionospheric densities in Titan's upper atmosphere

Abstract: . We find that on the dayside the solar energy deposition model overestimates the INMS-derived N + 2 production rates by a factor of 2. On the nightside, however, the model driven by suprathermal electron intensities from the Cassini Plasma Spectrometer Electron Spectrometer sometimes agrees and other times underestimates the INMS-derived N + 2 production rates by a factor of up to 2-3. We find that below 1200 km, all ion number densities correlate with the local ionization frequency, although the correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…It follows, similar to the situation addressed in the previous paragraph, that in order for the dayside and nightside comparisons of + N 2 production rates to become similar (i.e., for S day and S night to become similar), the solar EUV fluxes would need to be reduced (which would bring an issue on dayside + CH 4 production rate comparisons) and/or the suprathermal electron fluxes would need to be somewhat enhanced with respect to the CAPS/ELS measurements across the energy bins contributing the greatest to the ionization of N 2 . We note that Richard et al (2015a) found better agreement between dayside + N 2 production rates calculated from their solar energy deposition model and empirical chemical model than did Sagnières et al (2015). This is most likely due to a combination of various factors: the calibration factor for INMS ion number densities (updated factor used by Sagnières et al), different CH 4 and N 2 number densities, the correction factor in the empirical model from the inclusion of minor reactions, and a different solar flux model.…”
Section: Model-observation Comparison Of Electron Number Densities Inmentioning
confidence: 70%
See 4 more Smart Citations
“…It follows, similar to the situation addressed in the previous paragraph, that in order for the dayside and nightside comparisons of + N 2 production rates to become similar (i.e., for S day and S night to become similar), the solar EUV fluxes would need to be reduced (which would bring an issue on dayside + CH 4 production rate comparisons) and/or the suprathermal electron fluxes would need to be somewhat enhanced with respect to the CAPS/ELS measurements across the energy bins contributing the greatest to the ionization of N 2 . We note that Richard et al (2015a) found better agreement between dayside + N 2 production rates calculated from their solar energy deposition model and empirical chemical model than did Sagnières et al (2015). This is most likely due to a combination of various factors: the calibration factor for INMS ion number densities (updated factor used by Sagnières et al), different CH 4 and N 2 number densities, the correction factor in the empirical model from the inclusion of minor reactions, and a different solar flux model.…”
Section: Model-observation Comparison Of Electron Number Densities Inmentioning
confidence: 70%
“…Modeled + N 2 production rates on the dayside are higher (by a factor of ∼1.5-2) than derived from an empirical chemical model. On the nightside the situation is reversed, with the modeled production rates being lower than values from the empirical chemical model by a multiplicative factor of ∼0.4-0.7 (Sagnières et al 2015). 3.…”
Section: Summary and Concluding Remarksmentioning
confidence: 93%
See 3 more Smart Citations